ENGOT-OV16/NOVA trial of niraparib in recurrent ovarian cancer: survival and long-term safety - Matulonis, Ursula A.; Herrstedt, Jørn; Oza, Amit; Mahner, Sven; Redondo, Andrés; Berton, Dominique; Berek, Jonathan S.; Haslund, Charlotte A.; Marmé, Frederik; González-Martín, Antonio; Bécourt, Stéphanie; Tinker, Anna V.; et al. (Gynecologic oncology, 2025)
Objective - To evaluate secondary efficacy endpoints and safety for the ENGOT-OV16/NOVA (NCT01847274) trial of niraparib maintenance therapy after extended follow-up and vital-status-data retrieval. Previously reported analyses (data cutoff, October 1, 2020) indicated benefit of niraparib maintenance therapy beyond first progression, but overall survival (OS) analyses were limited by missing data. - Methods - Patients were randomized 2:1 to niraparib (300mg once daily) or placebo. A vital status check was extended to retrieve last-known-alive status for patients with missing survival data. Prespecified secondary efficacy outcomes (OS, chemotherapy-free interval [CFI], time to first subsequent therapy [TFST], PFS2, time to second subsequent therapy [TSST]) and safety are reported based on the extended data cutoff (March 31, 2021). - Results - Survival status was available for 97.6% (540/553) of randomized patients (germline BRCA [gBRCA]-mutated, 203; non-gBRCA-mutated, 350). Median OS with niraparib and placebo was 40.9 and 38.1months, respectively, in the gBRCA-mutated cohort (hazard ratio [HR], 0.85; 95% confidence interval [CI], 0.61-1.20) and 31.0 and 34.8months, respectively, in the non-gBRCA-mutated cohort (HR, 1.06; 95% CI, 0.81-1.37). Medians for CFI, TFST, PFS2, and TSST numerically favored niraparib in both cohorts. No new safety signals were detected. - Conclusions - OS did not significantly differ between treatment arms. Prespecified secondary efficacy endpoints numerically favored niraparib. Long-term safety remained consistent with the established niraparib safety profile. Taken together with the significant improvements in PFS observed in the primary analysis, these data support a favorable overall benefit-risk profile for niraparib in the recurrent OC maintenance setting.
Online veröffentlicht: 25. März 2025, Artikelversion: 25. März 2025
Gesehen am 23.06.2025